Faster Integer Programming. - Monroe, Don (Communications of the ACM, 2024)
This article examines the current work being conducted on improving integer programming with linear programming. Research conducted by Victor Reis and Thomas Rothvoss at the University of Washington utilizing an algorithm by Daniel Dadush is detailed. Topics include the incorporation of a technique from Ravi Kannan and László Lovász, as well as Noah Stephens-Davidowitz and Oded Regev’s contribution.